Advanced manufacturing and processing technology - Prakash, Chander; Singh, Sunpreet, 1989-; Davim, J. Paulo (Boca Raton, FL : CRC Press, 2021)
"This book disseminates recent research, theories, and practices relevant to areas of surface engineering and processing of materials for functional application such as aerospace, automobile, and biomedical. The book focuses on the hidden technologies and advanced manufacturing methods which may not be standardized by the research fraternity, however, are greatly beneficial to the material and manufacturing industrial engineers in different aspects. It provides such projects, research activities, and innovations on a global platform to strengthen the knowledge of the concerned community. The book covers surface engineering including coating, deposition, cladding, nanotechnology, surface finishing, precision machining, processing, and emerging advanced manufacturing technologies to enhance the performance of materials in terms of corrosion, wear and fatigue. The book has capture emerging areas of materials science and advanced manufacturing engineering and presents the recent trends in research for young researchers, field engineers, and academic professionals"--
4.3.1.2 Tool Material -- 4.3.1.3 Tool Feed Mechanism -- 4.3.1.4 Abrasive Slurry System -- 4.3.1.5 Oscillating System -- 4.3.1.6 Process Parameters -- 4.3.1.7 Effect of Process Parameters on Material Removal Rate -- 4.3.1.8 Advantages -- 4.3.1.9 Limitations -- 4.3.1.10 Applications -- 4.3.2 Abrasive Jet Micromachining -- 4.3.2.1 Working Principle -- 4.3.2.2 Process Parameters -- 4.3.2.3 Abrasive Material -- 4.3.2.4 Gas Medium -- 4.3.2.5 Nozzle -- 4.3.2.6 Effect of Material Removal Rate -- 4.3.2.7 Advantages -- 4.3.2.8 Limitations -- 4.3.2.9 Applications -- 4.3.3 Electrochemical Micromachining
OCLC-licensed vendor bibliographic record.
Keywords: Manufacturing processes; Materials science; TECHNOLOGY / Manufacturing; TECHNOLOGY / Material Science